2019
DOI: 10.1039/c9tb00473d
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione from recovered glucose as ingredient in antioxidant nanocapsules for triggered flavor delivery

Abstract: Side streams from modern lignocellulose biorefineries have found value-added applications in various industries ranging from food to medical. Here, bioproduction of glutathione from glucose recovered from man-made cellulose fiber production was investigated. Rayon fibers were enzymatically hydrolyzed and the resulting glucose and Zn in the hydrolysate were successfully used for glutathione (15.5 mg L À1 ) production by an engineered strain of Saccharomyces cerevisiae. Next, out of reduced glutathione (GSH) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In addition to the new carrier materials mentioned above, more materials were being discovered and studied, such as glutathione (GHS), because GHS has the antioxidant effect of scavenging free radicals, so it is more and more used in medicine, food and cosmetics industry (Tallian et al, 2019). Petzold et al (2014) found that the two different embedding layers of liquid smoke were obtained by titration of calcium alginate and calcium alginate-chitosan film.…”
Section: Jackfruit Seed Starchmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the new carrier materials mentioned above, more materials were being discovered and studied, such as glutathione (GHS), because GHS has the antioxidant effect of scavenging free radicals, so it is more and more used in medicine, food and cosmetics industry (Tallian et al, 2019). Petzold et al (2014) found that the two different embedding layers of liquid smoke were obtained by titration of calcium alginate and calcium alginate-chitosan film.…”
Section: Jackfruit Seed Starchmentioning
confidence: 99%
“…In addition to the new carrier materials mentioned above, more materials were being discovered and studied, such as glutathione (GHS), because GHS has the antioxidant effect of scavenging free radicals, so it is more and more used in medicine, food and cosmetics industry (Tallian et al, 2019).…”
Section: Flavor Encapsulationmentioning
confidence: 99%